RESEARCH INFRASTRUCTURES IN THE GLOBAL SPOTLIGHT- CHALLENGES AND OPPORTUNITIES FOR AGRICULTURE, BIOECONOMY AND RURAL DEVELOPMENT - Maria Luiza PASCAL; Adrian TUREK-RAHOVEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Research infrastructures are considered the pathway towards a prosperous economy and societal well-being in a long-term perspective. Based on these grounds, the European Commission emphasizes the role and importance of setting-up research infrastructures, at both European and International level, by promoting scientific excellence and frontier research. In this context, the purpose of this article is to present the framework and features of such research infrastructures. The document conveys the full involvement and commitment from the European Commission, in both financially and strategic terms, to build specific research infrastructures with the aim of addressing the big challenges that modern society faces in a fast-changing environment. Nevertheless, in spite of all efforts made, the financial sustainability still remains the main issue to which the decision-makers have to come up with solutions and ways of making these infrastructures everlasting in order to fulfil their mission, to achieve great objectives and priceless results for the benefit of the whole society.